Pengaruh Promosi Terhadap Peningkatan Penjualan Pada PT. Daya Adicipta Wisesa - Hariman, Jill Klara; Manoppo, Wilfried S.; Keles, Dantje (Sam Ratulangi University, 2019)
This study aims to measure the level of significance of the effect of promotion on increasing sales along with the magnitude of its influence. This research is quantitative descriptive by interpreting the results of simple correlation and regression analysis to see the relationship between the measured variables. While the sample used was 50 people, taken from 15 employees and 35 selected customers. From the data analysis found the significance value between the two variables X to Y is equal to 0,000 <0,05, it can be seen that the effect of promotion on increasing sales at PT. Daya Adicipta Wisesa is very significant. And for the amount of influence from variable X to Y, it can also be seen from the constant value that is equal to 6.332. This means that if the influence of variable X does not change, then the value of sales is only 63.32%. Meanwhile, the coefficient value is 0.730, which means that if the promotion conditions increase by 1, then the effect on the increase in sales will also increase by 73%. From these results, the decision making on the hypothesis, namely H0 is rejected and accepts Ha which states that promotion has a significant influence on increasing sales at PT. Daya Adicipta Wisesa.